Angel sharks (Squatinidae): A review of biological knowledge and exploitation. Issue 3 (4th January 2021) - Ellis, Jim R.; Barker, Joanna; McCully Phillips, Sophy R.; Meyers, Eva K. M.; Heupel, Michelle
Abstract: Angel sharks ( Squatina spp.) are distributed in warm temperate to tropical waters around the world. Many species occur in shelf seas and exhibit seasonal inshore–offshore migrations, moving inshore to give birth. Consequently, there can be high spatial overlap of angel shark populations with fisheries and other human activities. Their dorso‐ventrally flattened body shape, large size (most species attain >100 cm total length, L T ) and demersal nature means that they may be taken in a variety of demersal fishing gears from birth. Available data indicate that angel sharks typically have a biennial reproductive cycle, with litter sizes generally <20 and the young born at c . 20–30 cm. The biological characteristics of angel sharks render them susceptible to overexploitation, as exemplified by the decline of Squatina squatina from many parts of its former range in the north‐east Atlantic and Mediterranean Sea. Currently, half of the 22 recognized extant species of angel shark are classed as Threatened on the International Union for Conservation of Nature (IUCN) Red List (with a further three classified as Data Deficient). Given the biological vulnerability of angel sharks, and that many species are data‐limited, the current paper provides a review of available biological information and fisheries data pertaining to this family.